Mercury Identification Training and Safe Cosmetics Education for Babunnajah Vocational School Students.: Pelatihan Identifikasi Merkuri dan Edukasi Kosmetik Aman bagi Siswa SMK Babunnajah - Stiani, Sofi Nurmay; Oktaviana Hadi, Agriyaningsih; Yusransyah, Yusransyah; Subchan, Mohamad; Nurul Fitri, Nabila; Septina Sumantri, Aulia; Udin, Baha (Universitas Lancang Kuning, 2025)
The use of unsafe cosmetics among adolescents, particularly those containing mercury, remains a significant public health concern. This community service program aimed to enhance students’ knowledge at SMK Babunnajah through training in mercury identification and education on the safe use of cosmetics. The activity employed interactive lectures, group discussions, and hands-on mercury testing using simple reagent kits. An evaluation was conducted using pre-test and post-test questionnaires with 40 students. The results showed a substantial improvement in knowledge levels, with 70% of participants categorised as having high knowledge before the training, increasing to 100% afterwards. All knowledge indicators showed improvement, particularly in understanding product legality and the risks of mercury exposure. This training proved effective in fostering critical awareness and selective behaviour regarding cosmetic use. The program is recommended for replication in other vocational schools as a preventive measure against the use of illegal and harmful cosmetic products.